Minimum ten-year results of a 28-mm metal-on-metal bearing in cementless total hip arthroplasty in patients fifty years of age and younger - Innmann, Moritz Maximilian; Gotterbarm, Tobias; Kretzer, Jan Philippe; Merle, Christian; Ewerbeck, Volker; Weiss, Stefan; Aldinger, Peter R.; Streit, Marcus R. (International orthopaedics, 2014)
Concerns have been raised in relation to metal-on-metal (MoM) articulations with catastrophic soft-tissue reactions due to metal debris. We reviewed how small head MoM articulations perform in primary uncemented total hip arthroplasty (THA) in young patients at a minimum of ten years.
Gesehen am 07.09.2020
First published: 20 December 2013